Developing an integrated supply chain system for small businesses consortium in Australia: a service–oriented PHOENIX solution. (29th December 2014) - Li, Yongqiang; Dai, Wei; Armstrong, Anona; Clarke, Andrew; Du, Miaoli
Literature abounds with reports of the potential benefits that supply chain management creates for businesses worldwide. However, small businesses, whilst that they are the backbone of the Australian economy, are a backwater in the supply chain revolution, In particular, they are deprived of access to the benefits of the vertical integration of supply chains owing to size constraints, skill shortages, limitation in social networking and affordability. To address these issues and drawing on resource dependence theory and extant literature, the authors propose an integrated supply chain system for small businesses in Australia - a service–oriented PHOENIX solution. The paper contributes to knowledge by conceptualising the means of access and integration of supply chain management systems. The position paper also adopts scenario analysis in order to exemplify the potential applications and benefits of the proposed system. Giving consideration to the cost issue, the paper proposes that the PHOENIX system can be offered by small business consortiums, e.g., industry associations. Cloud computing and optimisation techniques will be applied to organise the time of use. The paper concludes by acknowledging the limitations and discussing future work.